2021
DOI: 10.3892/etm.2021.9896
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen‑to‑albumin ratio predicts long‑term outcomes for patients with ST‑elevation myocardial infarction and multivessel disease: A prospective observational cohort study

Abstract: The fibrinogen-to-albumin ratio index (FAR) is a valuable tool reflecting the systemic inflammation level and associated with the severity of coronary artery disease. However, the utility of the FAR in predicting the long-term prognosis of patients with ST-elevation myocardial infarction (STEMI) and multivessel disease has remained to be determined. A total of 424 patients diagnosed with STEMI and multivessel disease were recruited for the present study. They were given emergent percutaneous coronary intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It was found that, similar to traditional risk factors, plasma fibrinogen and albumin levels showed a close relation with the presence and severity of CAD [ 25 ]. The fibrinogen-to-albumin ratio index is a valuable biomarker associated with ST- elevation myocardial infarction and may be useful in the prediction of the long-term prognosis of patients with such diseases [ 26 ]. So, following the recent reports on humans discussed above and the results of the supplementation of fruits, it was shown that the triglyceride (TG)/cholesterol profile depended on the treatment of persimmon water extracts, and tannin-enriched persimmon concentrate stimulated hypocholesterolemic actions [ 6 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that, similar to traditional risk factors, plasma fibrinogen and albumin levels showed a close relation with the presence and severity of CAD [ 25 ]. The fibrinogen-to-albumin ratio index is a valuable biomarker associated with ST- elevation myocardial infarction and may be useful in the prediction of the long-term prognosis of patients with such diseases [ 26 ]. So, following the recent reports on humans discussed above and the results of the supplementation of fruits, it was shown that the triglyceride (TG)/cholesterol profile depended on the treatment of persimmon water extracts, and tannin-enriched persimmon concentrate stimulated hypocholesterolemic actions [ 6 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The albumin-to-globulin ratio (AGR) is used as a prognostic marker in acute ischemic cardiovascular events. Investigations were directed to determine whether serum AGR, fibrinogen, and the fibrinogen-to-albumin ratio (FAR) are related to the presence and severity of coronary artery disease [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being a feasible marker, as well as a cheap one, FAR could be considered a potential alternative tool to amplify the prognostic sensitivity value in patients with STEMI [ 26 ]. In addition, Liu et al [ 27 ] studied the relationship between FAR and the SYNTAX score, demonstrating that there is a linear connection in this case, as well as benefits such as simplicity, efficiency and exhaustiveness. Furthermore, it has been suggested that high levels of pre-procedural FIB are an independent risk marker for contrast-induced kidney injury after catheterization in patients with ACS [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FAR values could also be used to improve risk stratification in patients with NSTE-ACS [ 17 ]. A prospective cohort study involving 562 patients showed that FAR was an independent risk factor for all-cause mortality in patients with ST-segment elevation myocardial infarction (STEMI) and multivessel disease and that it helped in guiding clinical strategies [ 23 ]. A nonlinear relationship between FAR and in-hospital mortality among critically ill patients with AKI was also observed by Xia et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%